Propuesta de mejora para la planta de tratamiento de aguas residuales (PTAR) de una empresa del sector cosmético (2019)
In this project the diagnosis of the wastewater treatment of the cosmetic company was first carried out, where the Critical parameters that do not comply with current regulations; Currently, the PTAR has a four-stage treatment process, in two of these stages, errors are evidenced due to the low control given to each by the operators. The shortcomings are reflected with the breach of Resolution 0631 of 2015, for parameters BOD5 and COD, these values being found at 6434 mg / LO2 and 9690 mg / LO2 respectively.